Public Stigma of COVID-19 and Its Correlates in the General Population of China - Tian-Ming Zhang (MDPI AG, 2021)
This study aimed to examine the profile of COVID-19-related public stigma and its correlates in the general population of China. A cross-sectional online survey was conducted in China from 7 May to 25 May in 2020. A total of 1212 participants from the general population completed the survey measuring their stigmatizing attitudes towards COVID-19, as well as knowledge and causal attributions of COVID-19. Univariate and multivariate analyses were performed to examine the correlates of COVID-19-related public stigma. A total of 31.8% of participants endorsed stigmatization towards people with COVID-19. Those who were of older age (t = −3.97, p < 0.001), married (F = 3.04, p < 0.05), had a lower level of education (F = 8.11, p < 0.001), and a serious psychological response (F = 3.76, p < 0.05) reported significantly higher scores of public stigma. Dangerousness (B = 0.047, p < 0.001), fear (B = 0.059, p < 0.001), anger (B = 0.038, p < 0.01), and responsibility (B = 0.041, p < 0.001) were positively associated with public stigma. This study shows that public stigma related to COVID-19 is prevalent in the general population of China. Actions against public stigma need to contain the spread of misinformation about COVID-19, alter inappropriate attributions, alleviate unfavorable reactions, and provide psychosocial support for the public.